2006
DOI: 10.1007/s10482-006-9124-4
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid as antifungal in Eremothecium and other yeasts

Abstract: Interesting distribution patterns of acetylsalicylic acid (ASA, aspirin) sensitive 3-hydroxy (OH) oxylipins were previously reported in some representatives of the yeast genus Eremothecium--an important group of plant pathogens. Using immunofluorescence microscopy and 3-OH oxylipin specific antibodies in this study, we were able to map the presence of these compounds also in other Eremothecium species. In Eremothecium cymbalariae, these oxylipins were found to cover mostly the spiky tips of narrowly triangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Also, when aspirin was added to Ascoidea, the sexual stage proved to be most susceptible to inhibition (Ncango et al, 2007), similar to what was found for Dipodascopsis Kock et al, 1998), Dipodascus (Van Heerden et al, 2007) and Eremothecium (Leeuw et al, 2007). This is to be expected, as aspirin is known to inhibit b-oxidation in mammalian mitochondria and therefore also 3-OH oxylipin synthesis (Glasgow et al, 1999).…”
Section: Oxylipins Mitochondria and Aspirin Inhibitionsupporting
confidence: 72%
See 3 more Smart Citations
“…Also, when aspirin was added to Ascoidea, the sexual stage proved to be most susceptible to inhibition (Ncango et al, 2007), similar to what was found for Dipodascopsis Kock et al, 1998), Dipodascus (Van Heerden et al, 2007) and Eremothecium (Leeuw et al, 2007). This is to be expected, as aspirin is known to inhibit b-oxidation in mammalian mitochondria and therefore also 3-OH oxylipin synthesis (Glasgow et al, 1999).…”
Section: Oxylipins Mitochondria and Aspirin Inhibitionsupporting
confidence: 72%
“…This has been suggested recently (Leeuw et al, 2007) by growth experiments with several yeasts with both energy generation options, such as the aspirin-sensitive, nonfermentative Asc. This has been suggested recently (Leeuw et al, 2007) by growth experiments with several yeasts with both energy generation options, such as the aspirin-sensitive, nonfermentative Asc.…”
Section: Hypothesismentioning
confidence: 87%
See 2 more Smart Citations
“…LDH measurements similarly demonstrated that 1 mM ASA reduced RHO cell injury after challenge with Candida . Although antifungal properties have been attributed to ASA in other studies [16-18, 25], its protective capabilities in an infection model have not been previously documented.…”
Section: Discussionmentioning
confidence: 99%